2015
DOI: 10.1007/s00542-015-2621-5
|View full text |Cite
|
Sign up to set email alerts
|

Electrical contact performance of MEMS acceleration switch fabricated by UV-LIGA technology

Abstract: telecommunication, radar, RF and defense systems, etc. (Li et al. 2012;Kim et al. 2012). In particular, MEMS acceleration switches can respond rapidly in specific applications without power consumption. For instance, Wang et al. (2013) developed a low-G horizontally-sensitive inertial micro-switch which switches on when an acceleration threshold is met. Fu et al. (2013) presented a novel MEMS inertial switch used for power management, which can be integrated with detection and control systems without power con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The results showed that the contact resistance was less than 5 Ω while the isolation resistance was more than 200 MΩ, and the maximum allowable current was up to 100 mA. Zhou et al [36] presented a micro-contact resistance model to investigate the contact performance of the latching switches. As seen in Figure 7, Currano et al [31] also designed a reset actuator driven by the current to unlatch the switch, although the device size was remarkably increased.…”
Section: Persistent Closed Inertial Micro-switchesmentioning
confidence: 99%
“…The results showed that the contact resistance was less than 5 Ω while the isolation resistance was more than 200 MΩ, and the maximum allowable current was up to 100 mA. Zhou et al [36] presented a micro-contact resistance model to investigate the contact performance of the latching switches. As seen in Figure 7, Currano et al [31] also designed a reset actuator driven by the current to unlatch the switch, although the device size was remarkably increased.…”
Section: Persistent Closed Inertial Micro-switchesmentioning
confidence: 99%
“…More recently, a combined c-AFM and simulation investigation used the ballistic transport equation to describe electron transport through a conductive doped ultrananocrystalline diamond tip and a graphene sheet [16]. Further, various analytical models have been proposed to describe current flow through technologically relevant devices such as microelectromechanical systems switches [17][18][19][20][21][22][23][24][25][26]. These models describe microcontacts, which have inherent roughness, as an array of smaller point-contacts, each of which is described by the intermediate transport theory.…”
Section: Introductionmentioning
confidence: 99%
“…The switches with a keep-close function can keep it closed after the acceleration event is over, thus improving the contact reliability. However, the keep-close function requires special constructions, such as the hook-shaped electrodes of the latching switches [ 6 , 7 , 8 ], the V-shaped beams of the bi-stable switches [ 9 , 10 ], and the valve-channel of the micro-fluidic switches [ 11 , 12 ], complicating the structure topology or working mechanism or fabrication method, thus reducing the threshold accuracy, as shown in Table 1 . The latching switch with a 50.59 g designed threshold value in Ref.…”
Section: Introductionmentioning
confidence: 99%